Pemanfaatan Perpustakaan Sekolah dalam Serial Animasi "Daitoshokan no Hitsujikai" (A Good Librarian Like a Good Shepherd) - Indraji, Muhammad; Mayesti, Nina (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2017)
This study discusses the use of school libraries and the use of library clubs (books club) which is represented in the animated series "Daitoshokan no Hitsujikai” (A Good Librarian Like A Good Shepherd). This research is a qualitative research with framing analysis approach. The result shows that this animation serial represented school library purpose and utilization, especially in books club activities as one part of school library. The function and utilization of school libraries is represented through framing analysis tools. Framing analysis tools more focus on the metaphorical analysis contained in this animated series. The metaphorical analysis in this study is supported by story analysis, tradition analysis, slogan analysis, artefact or fact analysis, contrast elemental analysis in this animated series, prejudice analysis of the audience after watching this animated series, and analysis of the function and utilization of the library depicted in the animated series. These analyzes are assisted by the analysis of the idea elements contained in the animated series. In addition, in the animated series is shown the idea that the school library can be a center of activity in the school environment. On the other hands, in this animation serial showed an idea that school library can became a center-of-activities in school environment.